Multiple Plane Waves Expansion Method for Dispersive Media - Guryev, I. V.; Sukhoivanov, I. A.; Gnatenko, A. S.; Lipkina, V. I. (Begell House, 2008)
This paper presents the multiple plane waves expansion method. The method is based on plane waves expansion technique but it oriented primarily to the computation of band structures of photonic crystals containing dispersive materials. The verification of the method is also given in the work by comparison of results obtained for the same photonic crystal by multiple plane waves expansion method and by the finite difference time domain method with recursive convolution. Results obtained in the work show high accuracy of the method as well as its high performance and universality.
Keywords: photonic crystal; band structures; dispersive material